Risk adjustment of health-care performance measures in a multinational register-based study: A pragmatic approach to a complicated topic. (8th March 2014) - Moger, Tron Anders; Peltola, Mikko
Objectives: Health-care performance comparisons across countries are gaining popularity. In such comparisons, the risk adjustment methodology plays a key role for meaningful comparisons. However, comparisons may be complicated by the fact that not all participating countries are allowed to share their data across borders, meaning that only simple methods are easily used for the risk adjustment. In this study, we develop a pragmatic approach using patient-level register data from Finland, Hungary, Italy, Norway, and Sweden. Methods: Data on acute myocardial infarction patients were gathered from health-care registers in several countries. In addition to unadjusted estimates, we studied the effects of adjusting for age, gender, and a number of comorbidities. The stability of estimates for 90-day mortality and length of stay of the first hospital episode following diagnosis of acute myocardial infarction is studied graphically, using different choices of reference data. Logistic regression models are used for mortality, and negative binomial models are used for length of stay. Results: Results from the sensitivity analysis show that the various models of risk adjustment give similar results for the countries, with some exceptions for Hungary and Italy. Based on the results, in Finland and Hungary, the 90-day mortality after acute myocardial infarction is higher than in Italy, Norway, and Sweden. Conclusion: Health-care registers give encouraging possibilities to performance measurement and enable the comparison of entire patient populations between countries. Risk adjustment methodology is affected by the availability of data, and thus, the building of risk adjustment methodology must be transparent, especially when doing multinational comparative research. In that case, even basic methods of risk adjustment may still be valuable.